DIASPORA PHILANTHROPY AND ITS INFLUENCES: AN AUSTRALIAN PERSPECTIVE - Baker, Christopher; Mascitelli, Bruno (The journal of contemporary issues in business and government, 2011)
Diaspora philanthropy is a growing global phenomenon. A number of international publications in the last decade have begun to examine diaspora philanthropy for what it might tell us about how diaspora communities give. However, there is a dearth of studies relating to diaspora philanthropy within Australia. This exploratory study seeks to address that gap. This study engages with the emerging field of theoretical and empirical enquiry in relation to diaspora philanthropy by seeking to understand aspects of the phenomenon, via reference to three specified diaspora communities within Australia. We find that available data is largely inconsistent and unreliable. Initial evidence indicates that the genesis of a diaspora influences giving practices. We also find evidence that the giving practices of the sample diaspora in this study change in nature with time and the weakening of original ties that accompanies the passing of generations.